2008
DOI: 10.3945/jn.108.093781
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy-Induced Hyperphagia Does Not Modulate Bone Mineral Density or Bone Strength in Rats

Abstract: The ovariectomized (OVX) rat is a widely used animal model for the development of prevention and treatment strategies for postmenopausal osteoporosis. However, ovariectomy-induced hyperphagia results in weight gain and adiposity. To prevent potential protective effects of increased body weight on bone from confounding outcomes of preclinical studies, pair-feeding is used in some but not all studies to control food intake, but its importance is not well elucidated. We investigated if the type of feeding, pair-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
10
34
1
4
Order By: Relevance
“…Our findings are in accordance with recent studies where significant effects of oestrogen deficiency have been shown in ovx groups that were also not weight matched to the control group. 13,14 Despite the negative correlation of increased fat mass and fracture risk shown in epidemiological studies, 15 it is unlikely that the moderate ovx-induced weight gain affects the bone microarchitecture in mature rats that had already reached their peak bone mass before surgery. 16 We selected the proximal tibial metaphysis and the lumbar spine as the two skeletal sites for evaluation of morphological changes because they are often used in preclinical research for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with recent studies where significant effects of oestrogen deficiency have been shown in ovx groups that were also not weight matched to the control group. 13,14 Despite the negative correlation of increased fat mass and fracture risk shown in epidemiological studies, 15 it is unlikely that the moderate ovx-induced weight gain affects the bone microarchitecture in mature rats that had already reached their peak bone mass before surgery. 16 We selected the proximal tibial metaphysis and the lumbar spine as the two skeletal sites for evaluation of morphological changes because they are often used in preclinical research for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Bromodomain is an evolutionarily conserved, ~110 amino acid motif comprised of four left-handed, antiparallel α-helices [21]. The discovery of the drugability of bromodomains led to the screening of and identification of small molecules which can be used as bromodomain inhibitors in different epigenetic mechanisms.…”
Section: Effect Of Nmp On the Binding Ability Of Bromodomains And Betmentioning
confidence: 99%
“…Weights were comparable among all OVX groups prior to treatment, and weight gains over the treatment period were similar for all groups except CH and PG, which did not increase as much as the others. At both time points, animals in SV showed significantly lower weight compared to OVX groups, which was expected due to OVX--induced weight gain 274 . …”
Section: Gross Effectsmentioning
confidence: 64%
“…For instance, one role of estrogen is to strengthen satiation signals during meals by enhancing the effects of cholecystokinin (CCK), which is a peptide molecule released from the small 98 intestine during meals and binds to receptors on the stomach and duodenum 293 . An abnormal increase in appetite thus results from estrogen deficiency, and is known as hyperphagia 274 . In addition, because osteoblasts and adipocytes both originate from mesenchymal stem cells, and estrogen promotes the preferential differentiation of marrow mesenchymal stem cells into osteoblasts over adipocytes 28 , estrogen deficiency results in increased adipogenesis relative to osteoblastogenesis.…”
Section: Secondary Effectsmentioning
confidence: 99%